Jihad: Kajian Ontologis, Epistemologis, dan Aksiologis - Muhammad Ramadhan; Deni Firdaus; Anzil Alaina; Ahmad Rosyadi; Andi Rosa (Khulasah : Islamic Studies Journal, 2025)
In this article, the ontological, epistemological, and axiological studies of jihad in the philosophy of science are used to analyze the idea of jihad. From an ontological perspective, jihad is seen as a central idea in Islamic doctrine, which includes not only military conflict but also spiritual, moral, and social aspects. From an epistemological perspective, the meaning of jihad comes from reliable Islamic sources such as the Qur'an and hadith; however, in order to avoid being trapped in literal and extreme interpretations, it must be interpreted contextually using the maqashid sharia approach. On the other hand, jihad is studied from the perspective of values and goals in the axiological dimension, namely as a valiant effort to maintain humanity, justice, and a peaceful and inclusive society. This study shows how important it is to have a deep understanding of jihad in modern times to combat extremism, foster social cohesion, and give people more positive power. Therefore, it is necessary to redefine jihad based on current events while maintaining the core of the admirable principles of Islam.